Quality of Duck Manure Fertilizer and Paitan Leaves with the Addition of MOL Papaya Skin - Khairunnisa, Hana; Asngad, Aminah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The use of organic materials for the manufacture of fertilizers is an alternative to reduce waste in the environment. Fertilizer can be made using duck manure and paitan leaves (Tithinia diversifolia) which produce high levels of nutrients.The purpose of this study was to determine the quality of N,P, and K as well as sensory test results which included color, texture, pH, and aroma of duck manure and paitan leaves with the addition of papaya peel bioactivator.This study used an experimental research method with a completely randomized design (CRD) with a factorial pattern.The treatment factors were: Factor 1 weight of duck manure and sick leaves (B1: 300g duck manure+200g paitan leaves, B2: 200g duck manure + 300g paitan leaves), Factor 2: Addition of papaya skin waste bioactivator (P1: 25ml MOL of papaya skin waste , P2: MOL of papaya skin waste 30ml) data analysis used a qualitative descriptive study.The results showed that the best quality was the N test, namely the B1P2 treatment (5.34%), the P test, namely the B2P2 treatment (0.15%),the K test, namely the B2P2 treatment (0.47%).The results showed that the best quality was B1P2 which produced black fertilizer, loose texture, earthy aroma and had a pH of 6.